If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2x + -3) + -4 = 6x + 9x + -1 Reorder the terms: 8(-3 + 2x) + -4 = 6x + 9x + -1 (-3 * 8 + 2x * 8) + -4 = 6x + 9x + -1 (-24 + 16x) + -4 = 6x + 9x + -1 Reorder the terms: -24 + -4 + 16x = 6x + 9x + -1 Combine like terms: -24 + -4 = -28 -28 + 16x = 6x + 9x + -1 Reorder the terms: -28 + 16x = -1 + 6x + 9x Combine like terms: 6x + 9x = 15x -28 + 16x = -1 + 15x Solving -28 + 16x = -1 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. -28 + 16x + -15x = -1 + 15x + -15x Combine like terms: 16x + -15x = 1x -28 + 1x = -1 + 15x + -15x Combine like terms: 15x + -15x = 0 -28 + 1x = -1 + 0 -28 + 1x = -1 Add '28' to each side of the equation. -28 + 28 + 1x = -1 + 28 Combine like terms: -28 + 28 = 0 0 + 1x = -1 + 28 1x = -1 + 28 Combine like terms: -1 + 28 = 27 1x = 27 Divide each side by '1'. x = 27 Simplifying x = 27
| 30x-3x=X-2 | | 6x+15-7= | | 2(2n-1)=(n+3) | | 18+8x=9(x-2) | | 2(t-6)+6t=4(2t+3)-10 | | 3(9-3x)=45 | | x-5d=3 | | 6(-4x+5)=246 | | -77=7(1+4b) | | 4+3z-2=9z+9-7z | | 12+4(z-3)=3x+1 | | 5(r+3)-6=3(r-2) | | 3n+9=-3(2n+3) | | -28=7(7n-4) | | X^2=5*x^2-36 | | X+12+5x-17=2x+11 | | 7e^7t=11e^6t | | 5a+7b=17 | | 2(y+4)=21 | | 5*x^2-36-x^2=0 | | 3x-1=4x+9 | | x(x+3)-3=3x+1 | | 14-x=37 | | 7y-3=17 | | x^2+kx+8=k | | 5(m+4)-7= | | 5*x^2-x^2=36 | | 2(x^2-192)=0 | | .66d+1=16-d | | 2(x-3)+5=4x+7 | | -(a-4)=6 | | 10(a+1)-14a=9+(4a-1) |